The Implementation of a Positive Discipline Program To Increase the Social Skills of Middle Grade Students - Forbes, Reginald D. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1996)
A practicum project implemented a program designed to reduce negative behavior in the hallways and cafeteria of an urban middle school. The objectives of this program were to reduce by 15% the number of infractions in the cafeteria and in the hallway and to reduce by 15% the number of students suspended out of school. The target population was a group of approximately 900 students in grades 6 through 8. Students were taught social skills and given lessons on respect and proper decorum in the hallway and cafeteria. The effectiveness of this program was measured by discipline records reflecting student infractions and suspensions, and a pre- and post-intervention survey given to the staff. The results of this evaluation indicated that not all of the program objectives were met. However, there were improvements in all areas. Continuation of this program is recommended with the following modifications: (1) getting teachers more involved in the process; (2) developing a check list for monitoring; and (3) implementing the project in the early part of the year. Contains 22 references. (MOK)
ERIC Note: Master's Final Report, Nova Southeastern University.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Behavior Change; Behavior Problems; Discipline Policy; Intermediate Grades; Interpersonal Competence; Junior High Schools; Middle School Students; Middle Schools; Program Effectiveness; Program Evaluation; Student Behavior; Teacher Role; Positive Discipline -- School Rules; Reports, Descriptive; Dissertations/Theses, Practicum Papers